Knowledge and Practice of General Practitioners and Internists about Helicobacter pylori infection in Guilan, Iran - Mansour Ghanaei1, Fariborz (Iranian Association of Gastroerterology and Hepatology, 2011)
BACKGROUND This study aims to elucidate the knowledge and practice of general practitioners (GP) and internists regarding diagnosis and treatment of Helicobacter pylori (H. pylori ) infection in a high prevalent area, with the intent to assist with future educational strategies for H. pylori infection. METHODS In this cross-sectional study in Guilan, a Northern Province of Iran, all GPs and internists in the city of Rasht were included. Questionnaires consisted of questions on demographic characteristics in addition to physicians’ knowledge and practice regarding H. pylori infection. The questionnaire was verified by a panel of experts, validated by the test-retest method, and distributed among participants. Scores higher than the mean score indicated good knowledge or attitude. Those lower than the mean score indicated poor knowledge and attitude. Data were collected and analyzed by SPSS version 14 software. RESULTS The mean (SD) knowledge and practice score of physicians was 12.1±3.13 and 2.37±1.54, respectively. Overall, 67.9% of GPs and 91.7% of internists exhibited good knowledge scores, while 72.4% of GPs and 95.8% of internists showed good practice. Physicians who used books or educational programs and had working histories of less than 10 years scored significantly higher in terms of mean knowledge. The mean practice score of physicians who worked in public units and had working histories of more than 5 years and those who had used books or educational programs was significantly higher. CONCLUSION Since H. pylori infection is prevalent in Iran and GPs’ practices are directly under the influence of knowledge, it is necessary to attempt to increase the level and quality of information among GPs by educational and Continuing Medical Education programs and seminars.